The difference knowledge about hand wash before and after counselling at student Class VII MTS Darul Huda Ponorogo - Hariyanto Hariyanto; Bunga Panjani (Jurnal Delima Harapan, 2014)
The health and hand cleanliness can prevent micro organism infectious anddecrease nosoc mial infectious frequency. However, some people don’t wash theircorrectly before doing activities.The research method which was pre experimental design. The totalpopulation was 461 students. The sample size was 198 students withproportionate stratified random sampling technique. The research was done byscoring, with value knowledge of student about hand wash, then given counselingabout hand wash and retesting students’ knowledge about hand wash. hipotesistested by paired t-tes statistical test by significance level p<0.05.Based on the research result it was gotten the knowledge before counselingabout hand wash, which was a good knowledgeable as many as 31 (15.7%),respondents who were knowledgeable enough as many as 65 (32.8%) andrespondents who had less knowledge as many as 102 (51.5.%) and aftercounseling about hand wash, which knowledgeable was as many as 194 (98%)and respondent which knowledgeable enough was as many as 4 (2.0%). The scoreof statistic test was significance 0.000<0.005. it means there was differentknowledge student about hand wash in MTS Darul Huda Ponorogo.There was different knowledge’s student and the average knowledge will bebetter, researchers suggested to students to apply hand wash in daily activity.